2009
DOI: 10.1111/j.1365-2702.2008.02737.x
|View full text |Cite
|
Sign up to set email alerts
|

Living with type 1 diabetes: perceptions of children and their parents

Abstract: Conducting child- and parent-centred qualitative research allows exploration of the perceptions and understanding of type 1 diabetes mellitus and the meaning ascribed by children and their parents who live with the condition. Diabetes is a lifelong, life-threatening condition that has a significant impact on children's and parents' lives. Developing a deeper understanding of their lives and experiences will enable the delivery of nursing care to meet their specific needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
120
0
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(132 citation statements)
references
References 23 publications
4
120
0
8
Order By: Relevance
“…Our findings confirmed that caregivers overwhelmed by higher levels of burden on the CB subscales perceived limited participation of the family in maintaining cultural-social contacts and free leisure. According to the study conducted by Marshall et al, parents indicate lack of freedom and liberty as losses resulting from diabetes in a child [30].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings confirmed that caregivers overwhelmed by higher levels of burden on the CB subscales perceived limited participation of the family in maintaining cultural-social contacts and free leisure. According to the study conducted by Marshall et al, parents indicate lack of freedom and liberty as losses resulting from diabetes in a child [30].…”
Section: Discussionmentioning
confidence: 99%
“…This is clearly inappropriate, even in adolescence, and contrasts with a study in the UK where parents needed to reassure themselves by constant checking, to the extent that some children felt that their parents were too controlling. [1] With the modern spring-loaded lancet devices, fingerprick testing is quite easy. In five cases the children were helped with fingerpricks, in eight with measuring their blood glucose results, and in four with both checking and recording their results.…”
Section: Discussionmentioning
confidence: 99%
“…All suddenly face complex technical challenges. [1] Later, the constant repetition of testing and insulin administration, unremitting dietary vigilance and careful adjustment of every aspect of living with the disease potentially become wearisome. [1,2] Many children over the age of 10 years administer their own insulin injections, [3] although some authorities believe that the parents should take complete control up to the age of puberty, i.e.…”
mentioning
confidence: 99%
“…Today, an estimated number of five million diabetics exist in Brazil, about 300 thousand of whom are younger than 15 years (2) . The consequences of having a child with diabetes in the family have been widely debated upon in the Brazilian and international contexts (3)(4) . Adequate disease management in this population has shown to be a challenge, mainly for the children themselves, due to the presence of inadequate behaviors skills and knowledge that collaborate towards non-adherence to treatment and to a significant increase in long-term complications (5) .…”
Section: Introductionmentioning
confidence: 99%